The Effect of Brand Image and Product Quality on Customer Loyalty with Purchasing Decisions as An Intervening Variable - Putri Sari Dewi; Catur Widayati (International Journal Labs, 2024)
This research aims to analyze the role of Brand Image and Product Quality on Customer Loyalty with purchasing decisions as an intervening variable with research on Quaker cereal customers in Jabodetabek. This research uses a marketing management theory approach and consumer behavior theory. The population of this research is people who have purchased and consumed Quaker instant cereal products who live in the Jabodetabek area with a sample of 240 respondents. Data analysis method using Structural Equation Model-Partial Least Square (SEM PLS). The research results show that brand image does not have a significant effect on purchasing decisions for Quaker products. Brand image does not have a significant effect on customer loyalty through purchasing decisions on Quaker products. Product quality has a significant effect on customers loyalty through purchasing decisions on Quaker products.